South Asian Islam and British multiculturalism - Ali, Amir (Routledge, 2016)
This book analyses South Asian Islam's engagement with the West, and Britain in particular. It traces the roots of British multiculturalism to South Asia and the Deobandi school of Islam. The work shows how the pattern of interaction that initially emerged between the Deobandi Muslims and the colonial British state in late-19th century replicated itself in the British society in the second half of 20th century. The monograph reflects upon Islam's 'compatibility' with liberal democracy as well as explores how it contributed to its origins in the Enlightenment ethos. A nuanced, sensitive and topical study, this book will be essential to understanding the world in the light of contemporary world events-Paris 13/11 and Charlie Hebdo attacks, the Danish cartoon controversy, and the Trojan Horse incident in certain British schools as well as the much earlier Rushdie affair. It will be of great interest to researchers and scholars of political science, religion, political Islam, British and South Asian Studies, and history.